Fortificación de Salchicha de Res tipo coctel utilizando Harina de Amaranto (amaranthus) y Quinua (chenopodium quinoa) - Jiménez Proaño, Inés Verónica (2018)
The present project was born with the purpose of increasing the protein levels of the beef sausage cocktail type (quinoa flour and amaranth flour) by replacing the traditional wheat flour. The elaboration of beef sausage cocktail type fortified using Amaranth (Amaranthus) or Quinoa flour (Chenopodium Quinoa). We chose these cereals because the protein content is much higher than wheat, also with this research is to take advantage of the high nutritional content using two types of flours and two types of soy proteins (isolated and concentrated). An AxB design was developed with two factors under study: types of flours and proteins. An organoleptic analysis was carried out in which the parameters evaluated were: odor, color, taste, texture and acceptability. This analysis was evaluated with 40 tasters where it could be determined that the best treatment is t6 (a3b2) corresponding to (29,69 % beef + 23.4% pork + 3.60% amaranth flour + 39.18% other ingredients + isolated soy protein 4.13%). For the fortification of beef sausage cocktail-type the following process was followed: washing and disinfection of equipment, reception of raw material, weighing, chopping, grinding, cuttereado (4-12 ° C) for 10 min, sausage, tied, cooking (75-80 ° C for 15 min), cooled (H2O , at 4 ° C), packed, stored (4-7 ° C). From the analyzes carried out, the results are detailed below: from the physical-chemical analysis: ash 3.62%; 14.7% protein; humidity 70.6%; fat 10.1%; total dietary fiber 1.72%; 0.3% carbohydrate. From the microbiological analysis: e. coli, staphilococcus aureus, salmonella, are within the limits allowed in the stabilized standards, parameters that indicate that the product does not present any danger to the health of the consumer, the cost of the beef sausage cocktail-type fortified with amaranth flour from 1Kg has a retail price of $ 4.82 ctvs, while in presentation of 500gr has a preserve of $ 2.41 ctv, expressing that the price of the elaborated product is at a lower price and accessible to all types of consumers